STUDI KOMPARATIF KONSEP BELAJAR DALAM PERSPEKTIF SYAIKH AL-UTSAIMIN DAN JEAN PIAGET DAN PENERAPANNYA DALAM PENDIDIKAN ISLAM: STUDI KOMPARATIF KONSEP BELAJAR DALAM PERSPEKTIF SYAIKH AL-UTSAIMIN DAN JEAN PIAGET DAN PENERAPANNYA DALAM PENDIDIKAN ISLAM - Ali Mufrodi; Muhammad Miftahuddin (Program Studi Pendidikan Agama Islam, 2023)
Abstract Among the most important things in the educational process is learning. It also plays an important role in maintaining the nation in the midst of increasingly fierce competition among other nations who advance first because of learning. Therefore, this research will discuss comparative learning from the point of view of two popular figures in the world of education, especially in learning problems. The research objective here is to describe the concept of learning in the perspective of Shaykh Al-Utsaimin and Jean Piaget. This study activity is included in the category of qualitative research in which this type of research is library research, namely research which main object is books or related literary sources. The method of analysis of this research uses the Comparative Method, which is intended to explain the relationship of two phenomena or systems of thought. From this study, the authors concluded that the results of the comparison of learning concepts from the two figures were complementary to one another. Shaykh al-Utsaimin views that learning is a process of seeking knowledge, in which the knowledge referred to prioritizes knowledge that comes from the creator of the universe, conveyed by God's messengers. Then, Piaget argued that the concept of learning is an act of forming knowledge, as well as activities within oneself that cannot be observed directly. As for its implementation in learning Islamic Religious Education, one of which is by teaching knowledge gradually and little by little. The point is that if students have mastered a science (initial material), then they are given other knowledge (new material or advanced material).